2011
DOI: 10.1007/s11481-011-9277-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Δ-9-tetrahydrocannabinol Administration Increases Lymphocyte CXCR4 Expression in Rhesus Macaques

Abstract: Cannabinoids have been reported to produce various immunomodulatory effects, which could potentially impact the host response to bacterial or viral infection. We have recently demonstrated that chronic Δ-9-tetrahydrocannabinol (THC; 0.32 mg/kg i.m., BID) decreased early mortality in rhesus macaques infected with simian immunodeficiency virus (SIV). However, the possibility that prolonged THC administration affects lymphocyte counts, phenotype, and proliferation indices has not been addressed. We examined expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Again, no effect of the drug was observed on lymphocytes subsets, naive versus memory cell subsets, or markers of proliferation or apoptosis of T-cells. The one difference that was found was an increase in expression of CXCR4 on CD4 and CD8 T-cells (LeCapitaine et al 2011). These animals were later infected with SIV after 17 months of chronic THC administration.…”
Section: Cannabinoids and Infectionmentioning
confidence: 99%
“…Again, no effect of the drug was observed on lymphocytes subsets, naive versus memory cell subsets, or markers of proliferation or apoptosis of T-cells. The one difference that was found was an increase in expression of CXCR4 on CD4 and CD8 T-cells (LeCapitaine et al 2011). These animals were later infected with SIV after 17 months of chronic THC administration.…”
Section: Cannabinoids and Infectionmentioning
confidence: 99%
“…Chronic administration of Δ9‐THC ameliorates the progression of simian immunodeficiency virus (SIV) disease [animal model of HIV], attenuates inflammation and plasma/CSF viral load, modulates gut‐specific mechanisms, and decreases morbidity and mortality of SIV infected macaques [Molina et al, ,b, 2014]. Moreover, prolonged Δ9‐THC administration increases T lymphocyte CXCR4 expression on both CD4 + and CD8 + T lymphocytes [LeCapitaine et al, ], and induces intestinal anti‐inflammatory miRNA expression profile during acute SIV infection of rhesus macaques [Chandra et al, ]. Additionally, the incidence of significant neuropathology and opportunistic infections was lower in SIV‐infected subjects chronically treated with Δ9‐THC compared to control subjects [Winsauer, ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, other than what appears to be better retention of body mass and attenuated inflammatory milieu, no significant alterations in immune phenotype were observed in animals administered Δ-9-THC for 28 days prior to and throughout the course of infection. In subsequent studies, we also demonstrated that chronic Δ-9-THC administration to uninfected macaques for up to 12 months did not alter lymphocyte subtypes, naïve or memory subsets, and proliferation and apoptosis of T lymphocytes when compared to time-matched vehicle-treated controls (LeCapitaine et al, 2011). However, those studies showed that chronic Δ-9-THC administration to naïve animals increased CD8+ and CD4+ lymphocyte expression of CXCR4.…”
Section: Cannabinoid Immunomodulation and Hivmentioning
confidence: 70%